Waste Line a newsletter campaign on ecological waste management - Guidaben, Agatha Nell V.; Teodoro, Luis
The country was literally down in the dumps in the year 2000. The Filipino-made ILOVEYOU computer virus had just wrought worldwide havoc, and the impeachment trial of then President Joseph Estrada had everyone glued to the television court proceedings.